Presumption of innocence in criminal proceedings (Journal of actual problems of jurisprudence, 2018)
This article examines the presumption of innocence in criminal proceedings. The presumption of innocenceof the accused has an important place in the implementation of the criminal proceedings. The presumption ofinnocence protsessualisty are constant discussions that relate to its logical and political nature, as enshrinedin the law and implementation mechanism tion. The presumption of innocence must "work" and whenapplied to the defendant procedural enforcement in a preliminary investigation.Keywords: The presumption of criminal proceedings, the investigator, the proof.